Nesting of REDD+ Initiatives : Manual for Policymakers - World Bank (World Bank, Washington, DC, 2021)
Tropical forest countries that seek to reduce deforestation and participate in REDD+ are being challenged to develop policies that conserve forests in the long term; create incentives for local actors to protect forests; and align forest policies with agricultural and rural development and other land-use policies. Developing a REDD+ implementation strategy requires consideration of government budgetary resources as well as the various types of international finance that are available to support REDD+. In assessing this landscape of potential funding sources, policymakers can determine which types of finance to access; which financing conditions they can realistically achieve; and within what time frame it can be done, given national circumstances and institutional constraints. Many countries are participating in, or hosting initiatives to reduce deforestation. Since 2007, when REDD+ was first considered in the negotiations of the United Nations Framework Convention for Climate Change (UNFCCC), several initiatives for implementing REDD+ have been developed. The REDD+ activities advanced under these initiatives have operated at various levels, ranging from the project level, (geographically demarcated areas within which an activity takes place), to subnational and/or country-wide programs. Many countries already have received, or are seeking, payments for subnational and national REDD+ results. Many of these same countries already host, or intend to host, REDD+ projects, which are usually developed by private actors.